حصر الأنواع الرعوية في غابة ضهر الخريبات (جبلة - اللاذقية) وتحديد أهميتها النسبية - محمد ياسين; طيبة نور (Latakia University Journal -Biological Sciences Series, 2016)
نفذ هذا البحث في غابة ضهر الخريبات بمنطقة جبلة في سورية في عامي 2014- 2015 بهدف حصر وجرد الغطاء النباتي العشبي، إذ اختيرت أربعة مواقع من الغابة. واعتمدت طريقة باركر في تقدير التغطية النباتية والتغطية النسبية، كما اعتمدت طريقة المربعات في تقدير الكثافة والتردد. جمعت العينات النباتية من الغابة وجففت ثم صنفت بالاعتماد على الفلورا المتوفرة. بينت نتئج البحث وجود 42 نوعاً تنتمي إلى 35 جنساً التي تنتمي بدورها إلى 16 فصيلة. كان عدد الأنواع النباتية المستساغة أعلى من عدد الأنواع النباتية غير المستساغة. سجلت الشويعرة المربعةL. Bromus squarrosus أعلى أهمية نسبية (28.3%) تلاها ذيل الثعلب Banks & Sol. Alopecurus urticulatus (15.1%) ثم الحليبةL. Euphorbia helioscopia (9.0%)، ويعتبر نباتي الشويعرة المربعة وذنب الثعلب جيدان من الناحية الرعوية بينما يعتبر نبات الحليبة عديم القيمة الرعوية. The research had been implemented in Daher Al Kheribat stand in Jableh area in Syria in 2014- 2015 with the aim to inventory and characterize the herbal vegetation cover. Four sites were chosen in the stand. We adopted Parker method to estimate the plant coverage and relative coverage, and the method of squares was adopted to estimate the intensity and frequency. Plant samples were collected from the stand and dried and then classified based on Flora available. 42 species were registered belonging to 35 genuses distributed in 16 families. The number of plant species palatable was higher than the number of plant species unpalatable. Bromus squarrosus L. recorded the highest relative importance (28.3%), followed by Alopecurus urticulatus Banks & Sol (15.1%) then Euphorbia helioscopia L. (9.0%), The Bromus squarrosus L plant and the Alopecurus urticulatus Banks & Sol are good pastoral while the Euphorbia helioscopia L. plant is worthless pastoral.